The Gender Equality Struggles in The Novel of Perempuan Berkalung Sorban and Gadis Pantai - Moh Muzakka; Suyanto Suyanto (POETIKA, 2020)
The struggling of gender equalities was discussed often in various disciplines and discourses, a part is in literature. This paper analyzes the gender equalities struggle in two novels: Abidah El-Khalieqy’s Perempuan Berkalung Surban and Pramoedya Ananta Toer’s Gadis Pantai. El-Khalieqy is a woman who has runs a pesantren “educational institute with a Moslem background” and Toer is a man who favors a nationalistic-socialist ideology, with an emphasis on literary realism. A literary -sociological and a feminist critical approach were used in analyzing both novels. The result of the analysis shows that gender struggle in the novel Perempuan Berkalung Sorban is caused by male oppression of women based on the explanation and interpretation of very patriarchal verses from the Al Qur’an (Islam religion). The gender struggle in novel Gadis Pantai is caused by male oppression of women based on feudalistic traditions, the woman as private property of men. Being placed in this feudalistic position, women then respond with struggles for equality.